Antifungal and anti-biofilm activity of designed derivatives from kyotorphin - Andrade, Vitor Martins de; Bardaji, Eduard; Heras, Montserrat; Ramu, Vasanthakumar G.; Junqueira, Juliana Campos [UNESP]; Santos, Jessica Diane dos [UNESP]; Castanho, Miguel A. R. B.; Conceicao, Katia (Elsevier B.V., 2020)
Kyotorphin (KTP, L-tyrosyl-L-arginine) is an endogenous analgesic neuropeptide first isolated from bovine brain in 1979. Previous studies have shown that kyotorphins possess anti-inflammatory and antimicrobial activity. Six kyotorphins-KTP-NH2, KTP-NH2-DL, ibuprofen-conjugated KTP (IbKTP), IbKTP-NH2, N-methyl-D-Tyr-L-Arg, and N-methyl-L-Tyr-D-Arg-were designed and synthesized to improve lipophilicity and resistance to enzymatic degradation. This study assessed the antimicrobial and antibiofllm activity of these peptides. The antifungal activity of kyotorphins was determined in representative strains of Candida species, including Candida albicans ATCC 10231, Candida krusei ATCC 6258, and six clinical isolates-Candida dubliniensis 19-S, Candida glabrata 217-S, Candida lusitaniae 14-S, Candida novergensis 51-S, Candida parapsilosis 63, and Candida tropicalis 140-S-obtained from the oral cavity of HIV-positive patients. The peptides were synthesized by standard solution or solid-phase synthesis, purified by RP-HPLC (purity >95 %), and characterized by nuclear magnetic resonance. The results of the broth microdilution assay and scanning electron microscopy showed that IbKTP-NH2 presented significant antifungal activity against Candida strains and antibiofllm activity against the clinical isolates. The absence of toxic activity and survival after infection was assessed after injecting the peptide in larvae of Galleria mellonella as experimental infection model. Furthermore, IbKTP-NH2 had strong antimicrobial activity against multidrug-resistant bacteria and fungi and was not toxic to G. mellonella larvae up to a concentration of 500 mM. These results suggest that IbKTP-NH2, in addition to its known effect on cell membranes, can elicit a cellular immune response and, therefore, is promising for biomedical application. (C) 2019 British Mycological Society. Published by Elsevier Ltd. All rights reserved.
Keywords: Analgesic peptide; Antibiofilm; Antimicrobial peptides; Toxicity